Evaluation of plasma trace elements and oxidant/antioxidant status in Boerboel dogs with hip dysplasia - R. A. Ajadi; J. L. Sanni; E. F. Sobayo; O. K. Ijaopo (Bulgarian Journal of Veterinary Medicine, 2020)
Changes in plasma concentrations of trace elements and oxidants/antioxidants were evaluated in twenty healthy Boerboels of both sexes and median age of 2 years. Antero-posterior and flexed lateral radiographs of the hip were obtained using digital x-ray machine and hip grading was done according to Fédération Cynologique Internationale (FCI) system. Blood was collected from the cephalic vein for determination of plasma concentrations of manganese (Mn), magnesium (Mg), copper (Cu), co-balt (Co), malondialdehyde (MDA), superoxide dismutase (SOD), glutathione (GSH), glutathione peroxidase (GPX) and Vitamin E. Correlation between the parameters was done using Pearson’s cor-relation. Eleven (11/20) of the Boerboel dogs had hip dysplasia (HD), comprising five (5/9) males and six (6/11) females. Plasma Mn, Cu and Co were insignificantly higher in Boerboels with normal hips than those with HD. MDA concentration was significantly (P<0.05) lower in Boerboels with normal hips (0.75 ± 0.84 µmol/L) than in dogs with HD (1.77 ± 0.78 µmol/L), while SOD was sig-nificantly (P<0.05) higher in Boerboels with normal hips (0.65 ± 0.22 U/mL) than with HD (0.32 ± 0.16 U/mL). It was concluded that there were differences in plasma oxidants/antioxidants between Boerboel dogs with normal hips and those with hip dysplasia suggesting their role in the pathogenesis of canine hip dysplasia